Kontribusi Kelincahan Terhadap Kemampuan Menggiring Bola Pemain Futsal Smp Negeri 2 Bengkulu Selatan - Feri, Novedtwo Fer; Asnawati, Asnawati; Personi, Megi (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
This study aims to determine the contribution of agility to the dribbling ability of SMP Negeri 2 South Bengkulu futsal players. correlation or correlational research is research that seeks to determine whether there is a relationship between two or more variables. the independent variable is agility with the dependent variable being dribbling ability. The type of sempel in this study uses total sampling technique. The sempel is all SMPN 2 Bengkulu Selata futsal players totaling 18 people. The instruments used in this study were agility and dribbling tests.The agility test and dribbling ability obtained rtable of 0.400 because the correlation coefficient between rxy = 0.96> 0.400 and a contribution of 96%, which means that the contribution of agility to the dribbling ability of SMP Negeri 2 South Bengkulu futsal players is significant and large. Thus the hypothesis that reads